Bank lending, macroeconomic conditions and financial uncertainty: Evidence from Malaysia - Ibrahim, Mansor H.; Shah Haneef, Sayed Sikandar (Elsevier BV, 2012)
In this paper, we examine the interrelations between bank lending, macroeconomic conditions and financial uncertainty for an emerging economy, Malaysia. Adopting time series techniques of cointegration, causality and vector autoregressions (VARs), we arrive at the following main results. We note long run positive relations between real output and both real bank credits and real stock prices. However, with slow adjustment of real output in responses to credit expansion or stock price increase and weak exogeneity of the latter two variables, both credits and stock prices can be persistently higher than their fundamental values. The phenomenon can be detrimental since it heightens market uncertainty. Our results suggest that heightened market uncertainty is negatively related to output in the long run and, on the basis of dynamics analysis, it is likely to depress real output, real credit and real stock prices. At the same time, we note significant dynamic impacts of interest rate shocks on other variables. Taken together, these results have important implications for macroeconomic performance and stability for the case of Malaysia.